A imigração sueca no Rio Grande do Sul entre o final do século XIX e início do século XX (1890-1915) - Oliveira, Jaqueline da Silva de (2022)
The thesis intends to address the issue of Swedish immigration in Rio Grande do Sul. From the bibliographic analysis and documental sources, we sought to investigate the arrival of Swedish immigrants, since the intense migratory flows that brought waves of Europeans towards the south of Brazil also attracted Scandinavian immigrants. According to previous research, with the help of digital humanities and Public History, it was found that the first Swedish immigrants who arrived in Rio Grande do Sul territory in 1890 settled in the region of the Serra Gaúcha. Later, a group headed for the northwest region of the state, in the territory of the Missions, and later part of this group ended up crossing the Uruguay River and settled in Argentina, where they founded the city of Oberá. Two cities were formed with the contribution of these Swedish immigrants in Rio Grande do Sul, Ijuí and Guarani das Missões, where until today you can find a significant number of descendants of these Swedish families living in the same area. These were groups that had moved during the period of massive immigration of Swedes to Brazil, between 1890 and 1911, but that were forgotten among groups that were much more numerically expressive, such as Italians, Germans and Poles.